Eggs When Young, Chicken When Old. Time Consistency and Addiction over the Life Cycle - Luca Piccoli; Silvia Tiezzi (Institute of Labor Economics (IZA), 2023)
This paper tests whether young and adult smokers have different time preferences, in particular with respect to time consistency. The recent introduction of Tobacco 21 law in the US were in part motivated by allegedly inconsistent time preferences of the young consumers. This research empirically tests this hypothesis using individual cigarettes consumption longitudinal data from RLMS, estimating a quasi-hyperbolic discounting rational addiction model for young and adult smokers separately. While our test rejects time inconsistency in the form of present-bias for both population groups, young smokers are found to discount future utilities much more than adults. From a life-cycle perspective, this is still a form of time inconsistency, which provides partial empirical support to the T21 law motivation, but also highlights how the quasi-hyperbolic discounting formulation might not be able to properly capture long-run time preferences.
Keywords: C23; D03; D12; 330; rational addiction; smoking behavior; time inconsistency; young vs adult smokers; GMM